Nepal earthquake 2015: experience of junior clinical year medical students of Patan Academy of Health Sciences (Journal of Patan Academy of Health Sciences, 2018)
Dilemmas regarding whether medical students’ participation ‘as doctor’ in disaster response is ethical remains unanswered. Although they prove to be an important addition to the workforce during such settings, their limited competency and likeliness to harm themselves and the patients in the process raises questions. Here we present our views on medical students’ involvement in disaster response based on our experiences at Patan Hospital, Patan Academy of Health Sciences (PAHS) during the Nepal earthquake 2015. Medical students play a crucial role in disaster management; however, they are not proficient in care for mass disasters. Nonetheless, being involved offered students first-hand experience on disaster response and also helped the disaster response by providing extra manpower. With more training, medical students can serve as a skillful workforce during disaster. The impact of regular drills strategically placed during medical school training in the curricula can be of immense help to build capacity for medical disaster response.